ANTINOMI KEWENANGAN PENYIDIK PEGAWAI NEGERI SIPIL (PPNS) DENGAN PENYIDIK POLRI DALAM SISTEM PERADILAN PIDANA TERPADU - Kholilur Rahman; Efendik Kurniawan (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2022)
In the context of law enforcement, the process of investigating criminal acts is one of the sub-systems in the criminal justice system in Indonesia, which has a significant and strategic position, because investigations are the main gate and the beginning of the criminal justice process. Civil Servant Investigators (PPNS) are also given the authority to carry out professional investigations, in addition to the investigative authority of Polri Investigators. The investigation authority becomes a problem after there are various antinomical or contradictory provisions. In that context, it is interesting to analyze by first discussing the position of PPNS based on the criminal justice system and then discussing the harmonization of the provisionsof PPNS authority with Polri investigators in an integrated criminal justice system. The research method used in this study is normative, using a statute approach and a conceptual approach.